Pengalaman Keluarga Dalam Memberikan Dukungan Pada Pasien Diabetes Militus Tipe 2 Di Wilayah Kerja Puskesmas Mandiangin Di Kota Bukittinggi : Studi kualitatif - Krismayenti, Wita; Oktorina, Rola; Dewi, Ratna (REAL in Nursing Journal, 2022)
Background: Diabetes mellitus (DM) is a chronic disease. It is characterized by blood glucose levels exceeding normal and metabolic disorders of carbohydrates, fats and proteins caused by relative or absolute deficiency of the hormone insulin. Diabetes mellitus results in absolute or relative insulin deficiency and impaired insulin function. Diabetes militus is classified into type 1 diabetes, type 2 diabetes, other types of diabetes and diabetes in pregnancy. Methods: This research used qualitative research methods with phenomenological approach. The data were collected through in-depth interviews with 7 participants consisted of 6 female partners and 1 male participant at 25-70 years. They had been selected by purposive sampling technique. The results of the interview were analyzed by using the Colaizzi method. Results: The results of the interview obtained 6 themes, namely 1) family support for sugar control, 2) the family’s response to DM patients,3) family response to illness, 4) family support for physical activity, 5) family support in controlling food, 6) family support in taking medicine.Conclusion: In short, it can be concluded that the participants had family experience in caring for diabetes mellitus patients knew how to motivate patients to regulate the diet and activities of diabetes mellitus patients. The most important was the patients’ adherent in taking medication and diet. Last. it is suggested that the diabetic patient's family to motivate and support the patient's diet so that the patient can overcome high sugar levels.